Internationalization Of Indian IT Multinationals - Singh, Abhishek (2009)
Indian IT industry has emerged to be a strong and influential player on the world map. The industry which did not existed a few decades ago is now a major exporter of software services to major markets. The Indian IT firms now seem to move beyond exporting and advance further into the international market. With the help of case study approach, this study tends to examine the internationalization of these firms. The dissertation is aimed to see how far the traditional theories of internationalization can explain their internationalization process and strategies. For this purpose two big Indian IT companies – Infosys and TCS have been chosen. This study has evaluated each company‟s internationalization motives, capabilities in operating internationally and internationalization strategies, and has derived implications for internationalization theories. This study concludes that as the firms evolve the motives and their relative importance varies among them. However, the main motive have came out to be of seeking resources, and acquiring new domain knowledge and technological assets, rather than to exploit their competitive advantages; like what traditional theories assumed. The capabilities possessed by these firms also conformed to the Dunning‟s eclectic paradigm; however they varied between the two companies. Further, among other findings, it also came to notice that the internationalization strategy could vary among firms. In our cases strategy of forming joint-ventures did not appealed to either firm, however the choice between green-field and acquisition varied between the two firms. Also, it was observed that Indian IT firms are now actively using acquisition as a major tool for advancing into the International market and for climbing up the value chain.